2018
DOI: 10.3389/fped.2018.00200
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Clinical and Genetic Spectrum of Steroid Resistant Nephrotic Syndrome: The PodoNet Registry

Abstract: Background: Steroid resistant nephrotic syndrome (SRNS) is a rare condition, accounting for 10–15% of all children with idiopathic nephrotic syndrome. SRNS can be caused by genetic abnormalities or immune system dysfunction. The prognosis of SRNS varies from permanent remission to progression to end-stage kidney disease, and post-transplant recurrence is common.Objectives: The PodoNet registry project aims to explore the demographics and phenotypes of immune-mediated and genetic forms of childhood SRNS, to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
93
3
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(109 citation statements)
references
References 50 publications
4
93
3
9
Order By: Relevance
“…Steroid resistance in the children with idiopathic NS is related to many factors including the histopathological lesions. Previous studies also confirmed that primary NS in children with steroid resistance was more common in patients with FSGS, MesPGN, and MPGN (14,(25)(26)(27). These results showed a significant rate of minimal changes in nephrotic syndrome in the steroid-resistant group (28,29).…”
Section: Steroid Resistance In Vietnamese Children With Nssupporting
confidence: 67%
“…Steroid resistance in the children with idiopathic NS is related to many factors including the histopathological lesions. Previous studies also confirmed that primary NS in children with steroid resistance was more common in patients with FSGS, MesPGN, and MPGN (14,(25)(26)(27). These results showed a significant rate of minimal changes in nephrotic syndrome in the steroid-resistant group (28,29).…”
Section: Steroid Resistance In Vietnamese Children With Nssupporting
confidence: 67%
“…Primary deficiency caused by mutations in COQ genes results in various manifestations and heterogenic symptoms from kidneys and the nervous and muscular systems [10]. Among the so far studied genes, 4: PDSS2 / COQ1 , COQ2 , COQ6 , and ADCK4 / COQ8B are associated with steroid-resistant nephrotic syndrome (SRNS)—they are mutated in about 1% of cases [2, 3]. Mutations in PDSS2 and COQ2 are also mostly associated with progressive encephalopathy, seizures, and hypertrophic cardiomyopathy, while ADCK4 disease typically manifests as an isolated nephropathy [11].…”
Section: Discussionmentioning
confidence: 99%
“…It can be hypothesised that in patients with refractory proteinuria of unknown origin early genetic screening for treatable defects such as presented could provide a highly practical tool for the therapy optimization, before the progression of kidney damage. The PodoNet consortium revealed a number of such Janus-faced genes presenting in an oligosyndromic manner (including WT1 , SMARCAL1 , ADCK4/COQ8B , COL4A3-5 , CLCN5 ), where incidental diagnosis through NGS screening allowed for identification of the causative mutation in patients lacking extrarenal manifestation(s) classically associated with the particular genetic defect [3]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The age at first disease manifestation and the rate of chronic kidney disease progression will strongly depend on the gene affected and the type of mutation. 3 However, posttransplantation disease recurrence, observed in one-third of patients with immune-mediated disease, does not occur in patients with genetic podocytopathies.…”
mentioning
confidence: 99%